Comment on "Performance evaluation of 3 optical particle counters with an efficient multimodal calibration method" (Heim et al.,2008) - Performance of improved counter - Mullins, Benjamin; Kampa, D.; Kasper, G. (Elsevier Ltd, 2012)
This comment adds performance data for a modified version of one of the optical particle counters investigated in Heim et al. (2008), namely the WELAS 2100. The new version was found to have a counting efficiency much closer to unity for larger particle sizes as well as some improvement in the lower 50% detection limit.